Energetics and Dynamics of the Low-Lying Electronic States of Constrained Polyenes: Implications for Infinite Polyenes - Christensen, Ronald L. (2013)
Steady-state and ultrafast transient absorption spectra were obtained for a series of conformationally-constrained, isomerically pure polyenes with 5–23 conjugated double bonds (N). These data and fluorescence spectra of the shorter polyenes reveal the N dependence of the energies of six (1)B(u)(+) and two (1)A(g)(−) excited states. The (1)B(u)(+) states converge to a common infinite polyene limit of 15,900 ± 100 cm(−1). The two excited (1)A(g)(−) states, on the other hand, exhibit a large (~9000 cm(−1)) energy difference in the infinite polyene limit, in contrast to the common value previously predicted by theory. EOM-CCSD ab-initio and MNDO-PSDCI semi-empirical MO theories account for the experimental transition energies and intensities. The complex, multistep dynamics of the 1(1)B(u)(+) → 2(1)A(g)(−) → 1(1)A(g)(−) excited state decay pathways as a function of N are compared with kinetic data from several natural and synthetic carotenoids. Distinctive transient absorption signals in the visible region, previously identified with S* states in carotenoids, also are observed for the longer polyenes. Analysis of the lifetimes of the 2(1)A(g)(−) states, using the energy gap law for nonradiative decay, reveals remarkable similarities in the N dependence of the 2(1)A(g)(−) decay kinetics of the carotenoid and polyene systems. These findings are important for understanding the mechanisms by which carotenoids carry out their roles as light-harvesting molecules and photoprotective agents in biological systems.